Simultaneous occurrence of nonepileptic and epileptic seizures during a single period of in‐patient video‐electroencephalographic monitoring. Issue 4 (1st September 2017) - El‐Naggar, Hany; Moloney, Patrick; Widdess‐Walsh, Peter; Kilbride, Ronan; Delanty, Norman; Mullins, Gerard
Summary: Epilepsy and psychogenic nonepileptic seizures (PNES) can coexist and may present in two forms: sequential and simultaneous. In sequential presentations, epileptic seizures (ES) are treated and PNES emerge later. Simultaneous recording of ES and PNES by video‐electroencephalogram (vEEG) is less well described. We retrospectively reviewed all patients diagnosed with PNES by vEEG following standard seizure induction practices over a 21‐month period. Within this cohort, we established the prevalence of coexisting epilepsy using clinical and electrographic data acquired from our epilepsy‐specific patient record. We identified patients with simultaneous PNES and ES recorded during a single vEEG admission, establishing the frequency and emergent timing of each type. Of our 262 monitored patients, 59 were diagnosed with PNES. Nineteen of the patients with PNES had coexisting epilepsy (prevalence rate of 7.3% or 32% of those with PNES). Sixteen patients had PNES and ES recorded during the same admission, and the remaining three patients had sequential PNES following successful treatment of ES. PNES occurred earlier (mean, within 1.21 days), with ES occurring later (mean, within 4.86 days). The simultaneous occurrence of PNES and ES recorded during a single admission is more common than previously reported. Identifying this group of patients may require a significantly longer period of vEEG monitoring and a detailed analysis of each individual's historical seizure events.